Dual-protection of a graphene-sulfur composite by a compact graphene skin and an atomic layer deposited oxide coating for a lithium-sulfur battery1. Issue 12 (28th March 2015) - Yu, Mingpeng; Wang, Aiji; Tian, Fuyang; Song, Hongquan; Wang, Yinshu; Li, Chun; Hong, Jong-Dal; Shi, Gaoquan
<x xml:space="preserve">Abstract</x> Lithium-sulfur battery based on the graphene-sulfur aerogel dual-protected by a graphene skin and an atom layer deposited oxide layer exhibits superior cycling stability, good rate capability and high coulombic efficiency.